Impacts of Textile Waste Water on Fingerlings of Fresh Water Reservoir - Azmat, Rafia; Bibi, Foozia (Asian Journal of Chemistry, 2013)
Dye wastewater as an organic persistent pollutant chosen to investigate the impact on fingerlings of Tilapia mossambica collected from Kanjheer Lake of Sindh (average length, 15-18 cm) and weight, 42-45 g) at laboratory scale. The non-treated dye waste water collected from the regular dye centers from local market. Experiments were conducted into the three replicates viz.; non-treated and treated by dye waste water till mortality of all the fingerlings. The treatment was designed into two sets (I) 1 % and (II) 10 % dye waste in fish aquarium. It was observed that the fingerlings exposed to 10 % of the dye waste experienced rapid death within 12 h. While those which exposed to 1 % the dye waste showed delay in the mortality rate. It was the reduction in the length and the weight with reddish injury symptoms in the skin of the fingerlings. The dissection of the fish showed that the liver, kidney, heart and intestine were dissolving and appeared as bubbles. Investigations suggested that the decrease in muscles or dissolve of other important organism can be related with decrease in the concentration of the total protein. An increase in the concentration of total lipids and glucose may be due to the abnormal metabolism under stress. Analysis of essential mineral ions showed that the sodium ions contents were decreases and the concentration of potassium, calcium and magnesium ions increases after the exposure period. From the present research, it is assumed that the textile dye waste water induced adverse effects on fingerlings nurseries of economically important fish.